The Design of Electronic Toll Collection System Based on Radio-Frequency Identification - Zhang Hui (Bulletin of Electrical Engineering and Informatics, 2013)
This paper first analyzes the current situation of highway electronic toll collection system of domestic and international, depth research on some of the key technologies of Radio-frequency identification (RFID), establish electronic toll collection system based on RFID, RFID in the ETC of city application, on the one hand, greatly improved the image of city vehicle management, prevent manual vulnerabilities, on the other hand, greatly promoted the automation construction in city.